2020
DOI: 10.1038/s41388-020-01526-2
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 is necessary for androgen ablation-induced neuroendocrine differentiation from Pten null Sca-1+ prostate luminal cells

Abstract: Prostate adenocarcinoma undergoes neuroendocrine differentiation to acquire resistance toward anti-hormonal therapies. The underlying mechanisms have been investigated extensively, among which Sox2 has been shown to play a critical role. However, genetic evidence in mouse models for prostate cancer to support the crucial role of Sox2 is missing. The adult mouse prostate luminal cells contain both castration-resistant Sox2-expressing Sca-1 + cells and castration-responsive Sca-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
1
19
1
Order By: Relevance
“…While we cannot exclude that these lineages arise from early activation and/or leakiness of Pbsn-Cre, notably with respect to EMT-Gfp, there is compelling evidence through lineage tracing using luminal Nkx3.1-Cre and Krt8-Cre mice, and our spatial IF showing PANCK and SYP staining that transformed luminal cells readily transdifferentiate into NEPC (23). Specifically, and consistent with our data, L2 (SCA-1+) cells have an increased propensity to transdifferentiate to neuroendocrine cells upon androgen ablation compared with L1 (SCA-1-) (24).…”
Section: Main Textsupporting
confidence: 89%
“…While we cannot exclude that these lineages arise from early activation and/or leakiness of Pbsn-Cre, notably with respect to EMT-Gfp, there is compelling evidence through lineage tracing using luminal Nkx3.1-Cre and Krt8-Cre mice, and our spatial IF showing PANCK and SYP staining that transformed luminal cells readily transdifferentiate into NEPC (23). Specifically, and consistent with our data, L2 (SCA-1+) cells have an increased propensity to transdifferentiate to neuroendocrine cells upon androgen ablation compared with L1 (SCA-1-) (24).…”
Section: Main Textsupporting
confidence: 89%
“…Patterns of gene expression in the prostate have been shown to associate with anatomical and histological structure 18,28–30 . We and others demonstrated that several Wnt ligands were expressed at a higher level in the periurethral prostatic ducts (i.e., proximal ducts) than other ductal locations (distal ducts) 18,31 .…”
Section: Resultsmentioning
confidence: 96%
“…In the normal prostate, SOX2 expression is restricted to basal epithelial cells. It is repressed by canonical AR signaling [35][36][37] and conversely upregulated by AR signaling inhibitors [38] . SOX2 upregulation in prostate cancer has been associated with a poorly-differentiated stem-cell-like phenotype [35] and is necessary for castration-induced neuroendocrine differentiation in both PTEN null [39] and RB1/TP3 null [23] models of prostate cancer.…”
Section: Transcriptional Profile Of T-scncmentioning
confidence: 99%